Entrepreneurial Marketing Practices and the Performance of Small and Medium Enterprises in Kogi State - NAFIU, Ibrahim Olawale; ALOGWUJA, Cynthia Unekwu; ULOKO, Anthonia; OKPEBENYO, Bertha Mercy (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose: This study is aimed at the entrepreneurial marketing practices (EMP) and performance of small and medium enterprises (SMEs) in Kogi State.Methodology:A survey research design was used for the study. The researchers gathered data from 208 participants. The data collected were analyzed using descriptive statistics and multiple regression analysis.Findings: Findings showed that SMEs' proactive-ness (PROA) and customer satisfaction have a negative association. However, the relationship is insignificant (p>0.05). Risk-taking (RSKT) and innovativeness (INVT) of SMEs and customer satisfaction have a favorable link that is statistically significant (p<0.05).Implication:The study concludes that SME owners and managers must properly evaluate their EMP, which may be the possible cause of the inability to cope with the dynamic and competitive business climate. The study recommended, among others, that SME owners and managers embrace more innovativeness and risk-taking disposition to achieve improved performance relative to customer satisfaction and combine entrepreneurial marketing skills of risk-taking and innovativeness.